Tracking Local and Regional Influences of Potassium at the Korean Peninsula under Asian Continental Outflows during Spring - Jinsang Jung; Jihwan Kang (Aerosol and Air Quality Research)
Abstract The atmospheric stability of biomass-burning tracers such as K+ and levoglucosan is important in their application in assessing the impact of biomass-burning emissions in areas downwind of Asian continental outflows. It was found that levoglucosan in tested aerosol samples degraded ~48% at a suburban site in Daejeon, Republic of Korea within 31 h of exposure to ambient atmospheric conditions during spring, while K+ was stable under the same conditions. Analysis of aerosol samples collected at the same site during spring 2013 revealed that SO42- concentrations were moderately correlated with K+ concentrations, but not with levoglucosan concentrations. Air-mass backward-trajectory analysis showed that high SO42− concentrations at the sampling site were attributable mainly to long-range transported aerosols from the Asian continent. The poor correlation between levoglucosan and SO42− suggests that negligible amounts of levoglucosan might be transported from the Asian continent to downwind area of the Korean Peninsula during spring mainly due to the rapid degradation of levoglucosan during the long-range atmospheric transport. This result implies that levoglucosan is not a suitable tracer of biomass burning in area downwind of the Asian continental outflows during spring season. Levoglucosan/K+ ratios on the Asian continent and downwind on the Korean Peninsula indicate that ~39% of atmospheric K+ in Daejeon during spring 2013 was attributable to long-range transported aerosols from the Asian continent.